Clinical outcome changes in sarcopenic obesity: a meta-analysis of exercise training methods - Lei Chen; Haojing Zhou; Yichen Gong; Yi Tang; Hai Su; Zhongyi Zhang; Peijian Tong; Guoqian Chen (BMC Geriatrics)
Abstract Aim Assessing the effect of various forms of exercise training on patients with sarcopenic obesity. Methods Two independent reviewers systematically searched English and Chinese databases (PubMed, Embase, Cochrane Library, Web of Science, CNKI) for randomized controlled trials on various exercise training effects in sarcopenic obesity patients until October 2023. Reference materials and grey literature were also included. Selected studies underwent screening, data extraction, and quality assessment. Meta-analysis was conducted using Review Manager 5.4 software. Results A total of 8 studies were included in the final analysis. The Meta-analysis results indicated that resistance training (RT) significantly improved grip strength (MD = 3.85, 95%CI: 1.50 to 6.20, P < 0.01), percentage of body fat (MD = -2.96, 95%CI: -4.19 to -1.74, P < 0.01), walking speed (MD = 0.23, 95%CI: 0.01 to 0.46, P = 0.04), IGF-1(MD = 0.79, 95%CI: 0.05 to 1.52, P = 0.04) and knee extension strength (MD = 4.85, 95%CI: 1.97 to 7.72, P < 0.01). There was no statistically significant difference observed in weight (MD = -0.61, 95%CI: -4.06 to 2.84, P = 0.73). Aerobic training (AT) resulted in a significant reduction in weight among patients with SO (MD = -6.07, 95%CI: -9.89 to -2.25, P < 0.01), while no statistically significant differences were observed in other outcome measures. Mixed training (MT) significantly improved percentage of body fat (MD = -2.42, 95%CI: -3.58 to -1.26, P < 0.01), weight (MD = -4.40, 95%CI: -8.40 to -0.40, P = 0.03), IGF-1 (MD = 1.01, 95%CI: 0.45 to 1.56, P < 0.01), and walking speed (MD = 0.15, 95%CI: 0.04 to 0.26, P < 0.01). However, no statistically significant differences were observed in grip strength (MD = -0.70, 95%CI: -4.00 to 2.60, P = 0.68) and knee extension strength (MD = 1.73, 95%CI: -1.31 to 4.78, P = 0.26). RT, AT, and MT exercise could not significantly improve the level of serum IL-6 in patients with SO, and the difference was not statistically significant [MD = -0.01,95%CI:-0.27 to 0.24, P = 0.92]. Conclusion Various exercise training methods have differing effects on muscle-reducing obesity treatment. Compared to aerobic training, resistance training, and mixed training may offer more pronounced improvements, enhancing physical functioning in sarcopenic obesity patients. This underscores the clinical significance of exercise intervention in treating muscle-reducing obesity, suggesting future studies explore exercise intervention’s role and mechanism, particularly related to IGF-1, IL-6, and other cytokines.